Comparison Of The Effects Of Glucose And Coffee Toward Blood Glucose Levels And Muscular Endurance After Eccentric Activity - Ahmad Ilham Habibi; Ary Artanty; Afif Rusdiawan (IKIP Budi Utomo Malang, 2020)
The study aims to know the effects of glucose and coffe on blood glucose levels and muscular endurance after eccentric activity. The reseach subjects of badminton athletes PB MBC Malang fell 27 male athletes. Design (Randomized group pretest and posttest disign) is the research design chosen for this study. Glucose given before students do eccentric sports with a dose of 10 grams/70 kg BW, coffee given at a dose of 10grams/70kg BW. Eccentrie activity done by pulling up 2 sets, 7 repettions and 30 seconds interval. Blood glucose measured using a glucometer 3 times, while a pust up test chosen to measure the strength and endurance of the arm muccels carried out for 1 minute. LSD test results some significant comparisons on blood glucose variables between the control group with glucose p= 0,013, the control group with coffee p= 0,579. The endurance variable showed significant comparison in the blood glucose variable in the control group and the glucose group with a value of p= 0,005 and the control group with coffee giving of p= 0,026 while in the glucose and coffee group no significant effect with a value of 0,485.